Enhancing Voltage Profile and Power Loss Reduction Considering Distributed Generation (DG) Resources - Salman, M.; Hongsheng, S.; Aman, M. A.; Khan, Y. (Engineering, Technology & Applied Science Research, 2022)
In recent years, Distributed Generation (DG) has received attention due to its benefits to the distribution network. In this paper, the influence of DG along with several techniques for mitigating the detrimental impact on voltage profile and power losses was examined. The test system of 132 KV residential test feeder was selected, examined, and modeled in the Electrical Transient Analyzer Program (ETAP). Various tests were carried out to determine the influence of DG on the distribution network. Results were compared with, and without DG, taking into account the voltage profile. When injecting DG with unity power factor at different buses in a radial test system, it was discovered that when the DG of the right size and type is injected at the ideal position, the voltage profile improves while the power losses are reduced. When an un-deterministic DG is injected at multiple points on the test feeder, no improvement in voltage profile was observed. When the cross-sectional area of conductors is increased and a DG is injected at optimal locations, a positive impact on voltage profile is observed while the detrimental impact on power losses was also analyzed. The findings of this study may be useful to distribution firms regarding the future expansion of the power systems and the proliferation of DG.